2022
DOI: 10.3390/antiox11101912
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits and Pharmacological Properties of Stigmasterol

Abstract: Stigmasterol is an unsaturated phytosterol belonging to the class of tetracyclic triterpenes. It is one of the most common plant sterols, found in a variety of natural sources, including vegetable fats or oils from many plants. Currently, stigmasterol has been examined via in vitro and in vivo assays and molecular docking for its various biological activities on different metabolic disorders. The findings indicate potent pharmacological effects such as anticancer, anti-osteoarthritis, anti-inflammatory, anti-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 107 publications
1
51
0
Order By: Relevance
“…Hexadecanoic acid, which was detected in the chromatogram, is important in cell proliferation and has a variety of pharmacological effects such as anti-cancer and anti-microbial properties (27). The chromatogram revealed phytochemicals such as sitosterol (28) and stigmasterol (29) that are responsible for a wide range of pharmacological actions. Squalene, a notable triterpene compound with anti-oxidant and anti-tumor properties, was also identified in the GC-MS profile (30).…”
Section: Callus Induction and Maintenance Of Callusmentioning
confidence: 99%
“…Hexadecanoic acid, which was detected in the chromatogram, is important in cell proliferation and has a variety of pharmacological effects such as anti-cancer and anti-microbial properties (27). The chromatogram revealed phytochemicals such as sitosterol (28) and stigmasterol (29) that are responsible for a wide range of pharmacological actions. Squalene, a notable triterpene compound with anti-oxidant and anti-tumor properties, was also identified in the GC-MS profile (30).…”
Section: Callus Induction and Maintenance Of Callusmentioning
confidence: 99%
“…Studies have reported that stigmasterol can improve blood pressure and reduce the risk factors of cardiovascular diseases in postmenopausal women [ 70 ]. It can also improve blood glucose and induce β-cell regeneration by improving GLUT4 translocation and insulin resistance [ 10 ]. Furthermore, soy proteins and isoflavones also reduced blood cholesterol and triglyceride [ 71 , 72 ], which might be beneficial to cardiovascular health and systemic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acids, lecithin, and stigmasterol are also the main components of soy. Studies have reported that these ingredients can reduce the total cholesterol and low-density lipoprotein cholesterol levels, improve diabetes and protect cardiovascular health [ 9 , 10 ]. Soy foods are classified into fermented and non-fermented soy foods.…”
Section: Introductionmentioning
confidence: 99%
“…The phytosterol stigmasterol is classified as a tetracyclic triterpene. Its inflammation was reduced by releasing anti-inflammatory cytokines, reducing inflammatory mediator release, and inhibiting iNOS and COX2 ( 42 ). It has been demonstrated by several in vitro studies that beta-sitosterol possesses anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%